Apakah Pembatasan Sosial Berskala Besar Warga Negara Asing Berdampak Pada Average Abnormal Return? Studi Pada Sub Sektor Pariwisata, Perhotelan, dan Restoran di Bursa Efek Indonesia - Asnat Susanti Dangga Lolu; Lusianus Heronimus Sinyo Kelen (Jurnal Akuntansi Terapan dan Bisnis, 2021)
This study examines the differences in stock prices listed on the Indonesia Stock Exchange as measured using average abnormal returns on events (event studies) before and after the enactment of Large-Scale Social Restrictions for Foreign Citizens, especially COVID-19 which has an impact not only threatening human health but also has an impact on the economic sector. This condition will certainly have an impact on all sectors including stock trading on the Indonesia Stock Exchange, especially the Tourism, Hospitality, and Restaurant sub-sector. By using a sample of 41 companies on the Indonesia Stock Exchange with a research period of 3 months (16 November 2020 to 15 February 2021) the type of purposive sampling research that meets the criteria and using paired sample t-test, the results show that there is no difference Average Abnormal Return before and after the occurrence of a PSBB event for Foreign Citizens. So it can be concluded that the PSBB for Foreign Citizens has no impact on the average abnormal return obtained by investors.